Impulsividade e feedback autocontrolado na aprendizagem motora - Barbara de Paula Ferreira (2017)
In recent years, the self-controlled feedback benefits to motor skills learning havebeen investigated. These benefits can be related to a better engagement of learnersin differentiated strategies of self-regulation during the process of learning. In thiscontext, it is expected that individual differences such as the impulsivity level couldalter the usage quality of the self-controlled feedback, once that more impulsivepeople have inferior self-regulation ability. The aim of the present study was toinvestigate whether the level of learners impulsivity could alter the quality of use ofself-controlled feedback in the motor skill learning. Ninety participants answered theBarkley Deficits in Executive Functioning Scale. The sixty participants whoreached the lowest (33,3%) or highest scores (33,3%) in the impulsivity itempracticed the motor task. These participants were right handed, of both sexes, naïvein the task and with mean age of 23,3 ± 3,7 years. Four experimental groups werecreated by combining the impulsivity levels (more or less impulsive) and feedbacktype (self-controlled or yoked). The motor task consisted of sequential key press inpredetermined absolute and relative between keys times. The results indicated that,independently of impulsivity level, the use of self-controlled feedback was not moreeffective for learning. In transfer test, the less impulsive were better in absolutedimension, while the more impulsive had better performances in relative dimension.Therefore, the findings of the present study challenge the logic of the possible selfcontrolbenefits explanations. However, it was shown that individual characteristicsas impulsivity seems to favor the learning of distinct aspects of motor skills